Recent HIV infections: evaluation of a simple identification score for newly diagnosed patients - Elaine Monteiro Matsuda; Cintia Mayumi Ahagon; Luana Portes Ozório Coelho; Ivana Barros de Campos; Daniela Rodrigues Colpas; Andreia Moreira dos Santos Carmo; Luís Fernando de Macedo Brígido (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE Recognize incident infection to better characterize the groups that fuel HIV epidemic. We propose a simple score to identify recent infections among newly diagnosed patients as a HIV surveillance tool. METHODS Newly diagnosed patients were defined as recent infections when a negative serological test in the previous year was available. Laboratory tests, such as the avidity index (Bio-Rad, according to the CEPHIA protocol), chemiluminescent intensity (CMIA, architect, Abbott), and the nucleotide ambiguity index of partial pol sequences were used as proxies of recency. A simple score based on clinical symptoms of acute retroviral syndrome during the previous year, CD4+ T cell count, and viral load at admission was tested to assess the predictive power, using receiver operating characteristic (ROC) curves, to identify recent cases of infection. RESULTS We evaluated 204 recently diagnosed patients who were admitted to the Ambulatório de Referência em Moléstias Infecciosas de Santo André (Santo André Reference Infectious Diseases Outpatient Clinic), in the metropolitan region of São Paulo, Brazil, recruited between 2011 and 2018. An HIV-negative test in the year prior to enrollment was documented in 37% of participants. The proportion of cases classified as recent infections (less than one year), according to the laboratory proxies were: 37% (67/181) for an avidity index < 40%, 22% (30/137) for a CMIA < 200, and 68% (124/181) for an ambiguity index < 0.5%. Using different combinations of recency definitions, our score showed an area under the ROC curve from 0.66 to 0.87 to predict recency. CONCLUSIONS Using data from patients' interviews and routine laboratory tests at admission, a simple score may provide information on HIV recency and thus, a proxy for HIV incidence to guide public policies. This simple for the Brazilian public health system and other low- and middle-income countries.